MODEL PERKAWINAN SIRRI DAN AKIBAT HUKUM BAGI ANAK DAN ISTRI - Rizqi Suprayogi; Fredy Gandhi Midia ‎ ‎ ‎ (Syakhsiyah Jurnal Hukum Keluarga Islam, 2022)
Marriage has useful lessons for human life to achieve happiness for those who run it. So fostering a good and happy family is the dream ideal in every marriage. However, Islamic law often encounters difficulties in achieving these ideals in its journey. This is due to the fact that from the very beginning, the formation of marriage gave room for things to arise that mafsadatan arise in the household, such as unregistered marriages. This unregistered marriage has different models according to the intent of secrecy, whether the State does not register it, not published to the public, or there are no witnesses. The State does not accommodate the legal consequences of sirri marriages for children and wives. Therefore, protection for children and wives due to sirri marriages must be realized.